The Agulhas Current Transports Signals of Local and Remote Indian Ocean Nitrogen Cycling. Issue 3 (14th March 2023) - Marshall, Tanya A.; Sigman, Daniel M.; Beal, Lisa M.; Foreman, Alan; Martínez‐García, Alfredo; Blain, Stéphane; Campbell, Ethan; Fripiat, François; Granger, Robyn; Harris, Eesaa; Haug, Gerald H.; Marconi, Dario; et al.
Abstract: The greater Agulhas Current region is an important component of the climate system, yet its influence on carbon and nutrient cycling is poorly understood. Here, we use nitrate isotopes (δ 15 N, δ 18 O, Δ(15–18) = δ 15 N–δ 18 O) to trace regional water mass circulation and investigate nitrogen cycling in the Agulhas Current and adjacent recirculating waters. The deep and intermediate waters record processes occurring remotely, including partial nitrate assimilation in the Southern Ocean and denitrification in the Arabian Sea. In the thermocline and surface, tropically sourced waters are biogeochemically distinct from adjacent subtropically sourced waters, confirming inhibited lateral mixing across the current core. (Sub)tropical thermocline nitrate δ 15 N is lower (4.9–5.8‰) than the sub‐thermocline source, Subantarctic Mode Water (6.9‰); we attribute this difference to local N2 fixation. Using a one‐box model to simulate the newly fixed nitrate flux, we estimate a local N2 fixation rate of 7–25 Tg N.a −1, with the upper limit likely biased high. In the mixed layer, nitrate δ 15 N and δ 18 O rise in unison, indicating that phytoplankton nitrate assimilation dominates in surface waters, with nitrification restricted to deeper waters. Because nitrate assimilation and nitrification are vertically decoupled, the rate of nitrate assimilation plus N2 fixation can be used to approximate carbon export. Thermocline and mixed‐layer nitrate Δ(15–18) is low, due to both N2 fixation and coupled partial nitrate assimilation and nitrification. Similarly low‐Δ(15–18) nitrate in Agulhas rings indicates leakage of low‐δ 15 N nitrogen into the South Atlantic, which should be recorded in the organic matter sinking to the seafloor, providing a potential tracer of past Agulhas leakage. Plain Language Summary: The Agulhas Current is known to transport heat and salt from the warm tropics to the cooler (sub‐)polar regions, but little is known of its nutrient fluxes. Here we use new measurements of the essential phytoplankton nutrient, nitrate, and its isotope ratios to better characterize water circulation and the nitrogen cycle in the Agulhas Current and adjacent waters. Below 500 m, we see evidence of processes that occurred in other ocean basins. Above 500 m, we find that the nearby tropical and subtropical waters that feed the current have different chemistries and do not mix across its fast‐flowing core. In the sunlit surface layer, the dominant nitrogen cycle process is nitrate uptake by phytoplankton, while nitrification, which produces nitrate from organic matter, occurs only in the dark waters below the surface. Additionally, the Agulhas Current and adjacent waters host significant rates of N2 fixation, the process by which atmospheric N2 gas is converted to nitrogen forms that are useable by phytoplankton. This N2 fixation imprints a unique isotopic signature on the nitrate pool below the surface layer, which remains evident in Agulhas waters that enter the South Atlantic, potentially providing a tool to track Agulhas leakage, today and in the past. Key Points: Water masses in the greater Agulhas region have distinct biogeochemical properties that reflect local and remote nitrogen cycling Photosynthetic nitrate assimilation dominates the mixed‐layer nitrogen cycle while in situ nitrification is negligible Local N2 fixation and internal nitrogen cycling imprint a signal on Indian Ocean nitrate that can be tracked into the Atlantic Ocean